Centrality Effects in the Finance-Growth Nexus: Panel Data Evidence from Eastern and Southern African Countries - Alananga, Samwel; Mutasa, Felician (International Journal of Economics, Management and Accounting, 2024)
This study examines the moderating effect of spatial centrality (in trade) on the relationship between Financial Sector Development (FSD) and Gross Domestic Product (GDP) growth in Southern and Eastern African countries based on panel Error Correction Models (ECM) and a Panel Smooth Transition Regression (PSTR) model where centrality is used as a regime-switching variable. Data covering 1980 to 2022 were obtained from the World Development Indicators (WDI) and Comité Européen d’Etudes des Polyphosphates (CEPII). The centrality regime switching effect is found to be statistically significant, with the finance-growth nexus being negative via both broad money and credit to the private sector in center countries and positive via credit to the private sector in the periphery, an observation that supports the Convergent Growth Hypothesis (CGH) that countries in the periphery are catching up to Centers in terms of GDP growth. This long-run behavior is strongly endorsed by gross fixed capital formation, which has a long-run effect on GDP growth but is rarely supported by openness and working population, whose effect is country-specific. This study adds Geography and FSD as key explanatory variables of the local CGH, where periphery countries tend to catch up to relatively developed center countries within their respective regions.